Mothers' Care: Reversing Early Childhood Health Shocks through Parental Investments - Cristina Bellés-Obrero; Antonio Cabrales; Sergi Jimenez-Martin; Judit Vall-Castello (Center for Economic Studies and ifo Institute (CESifo), 2019)
We explore the effects of a child labor regulation that changed the legal working age from 14 to 16 over the health of their offspring. We show that the reform was detrimental for the health of the son's of affected parents at delivery. Yet, in the medium run, the effects of the reform are insignificant for both male and female children. The sons of treated mothers are perceived as still having worse health at older ages, even if their objective health status has recovered. These boys are also more likely to have private health insurance, which suggests more concerned mothers.
Keywords: J81; I25; I12; J13; 330; minimum working age; education; child health; gender